ENVIRONMENTAL HEALTH CONDITIONS AND LABOR’S HEALTH COMPLAINTS IN THE LUMBER INDUSTRY, SEMPU SUB-DISTRICT, BANYUWANGI 2018 - Adelina, Bayu Maharani (International Journal of Public Health Science (IJPHS), 2020)
Environmental health facility is a basic need for labor at various types of industries, including the lumber industry. Environmental health conditions are checked periodically by reference to applicable regulation. The target of this study is the lumber industry in Sempu Sub-District. This is based on the results of a preface study that the lumber industry in Sempu Sub-District has a condition which paid less attention to health facilities on the workplace. The purpose of this study was to determine the overview of environmental health conditions which carried out through assessment and identification of complaints due to environmental conditions such as noise and lighting. The field observation method was used through the measuring of the noise and lighting intensity, and the questionnaire for the health assessment sheet for the industrial environment. According to the results of the study, the intensity of light and noise did not meet the standards, and the results of the assessment were still insufficient category. Therefore, improvements in environmental health facilities are needed, as well as efforts for noise reduction, utilization of ear protection equipment for labor, and repairments of lighting systems for all work area, as needed.